2000
DOI: 10.1067/mva.2000.108634
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of a failed femoropopliteal bypass grafting: Comparison of saphenous vein and PTFE grafts

Abstract: Patients undergoing femoropopliteal bypass grafting with PTFE are at greater risk of ischemic complications from graft occlusion and more frequently require emergency limb revascularization as a result of graft occlusion than patients receiving SV grafts. Graft patency and limb salvage are superior with SV in comparison with PTFE in patients undergoing femoropopliteal bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(64 citation statements)
references
References 11 publications
3
59
0
2
Order By: Relevance
“…A similar scenario was shown when ePTFE grafts were compared with saphenous vein grafts for femoral-popliteal artery bypass. Investigators 16 found a higher incidence of patients presenting with grade II acute ischemia, and deterioration of arterial runoff when ePTFE grafts thrombosed, compared with their vein counterparts. Despite the encouraging results of endovascular therapy in the short term, long-term data are lacking.…”
mentioning
confidence: 97%
“…A similar scenario was shown when ePTFE grafts were compared with saphenous vein grafts for femoral-popliteal artery bypass. Investigators 16 found a higher incidence of patients presenting with grade II acute ischemia, and deterioration of arterial runoff when ePTFE grafts thrombosed, compared with their vein counterparts. Despite the encouraging results of endovascular therapy in the short term, long-term data are lacking.…”
mentioning
confidence: 97%
“…Apart from just patency rates, there has been little emphasis on the ischemic consequences of occlusion of a vein or PTFE bypass graft. It has been shown, though, that patients with occluded PTFE femoropopliteal reconstructions are at greater risk of limb-threatening ischemic complications and more frequently required emergency redosurgery than patients with vein-graft reconstructions [31]. Among several possible factors that might account for this, intermittent micro-thromboembolism from prosthetic grafts may lead to compromise of the tibial run-off.…”
Section: Type Of Graft and Patency Ratesmentioning
confidence: 94%
“…Bypasses to the suprageniculate popliteal artery segments can be performed with prosthetic grafts. However, despite a lack of significant differences in graft patency and limb salvage between autologous and prosthetic conduits in an above-knee configuration, controversy remains as to long-term performance and thromboembolic complications associated with prosthetic graft failure [25,26]. In addition, prosthetic bypasses should be avoided in patients with foot sepsis or active infection, in order to avoid arterial graft infection.…”
Section: Relative Roles Of Surgery and Endovascular Interventionmentioning
confidence: 98%